Pilot Testing on Leader-Member Relationships and Hospital Performance in A General Hospital of Traditional Chinese Medicine - Zhang, Na; Surienty, Lilis; Chun, Guang Xie (2022)
This research explores followers’ characteristics from doctors’ perspectives and the leader-member exchange imperative in the Hospital of Chengdu University of Traditional Chinese Medicine’s performance. LMX theory is employed in this article. This study’s focus groups comprised 10 participants, including five leaders and five members from the hospital. This research found that doctor followers’ conscientiousness impacted the quality of LMX and their performance. Moreover, conscientiousness, agreeableness, and extraversion were linked to positive affect, while neuroticism ad narcissism was linked to negative affect. Finally, positive affection positively impacts LMX and vice versa. The present study included two potential research limitations. First, personality was measured by the Big Five Factors; thus, the previous researchers could not analyze it in the real world. Second, although the researcher did have two sources of data (such as the doctor leader and doctor member), it is a possibility that the data collection may have influenced some of the proposition’s relationships because the data collected was limited. On the other hand, the study found that followers’ conscientiousness determined that the quality of LMX significantly impacted LMX and their performance. Leaders’ conscientiousness and extroversion can positively impact LMX.